Mistrzyni dyskrecji, znawczyni sztuki harmonii - Legeżyńska, Anna (Polonistyka. Innowacje, 2015)
The article presents the character of Julia Hartwig, a prominent war generation poet, born in 1921 and still extremely creative. The author of the article lists the most important information about her life, characterized by a poetic and translation achievements; the author also discusses the main features of Hartwig’s language and her attitude towards the world. The article draws attention to the role of memory and image. It also characterizes the ethical dimension of the poetry and the relationship with the great tradition of the European culture.